Avaliação de um programa de residência médica em ginecologia e obstetrícia - Sanchez, Natalia Romano (2019)
Medical residency is an essential part of training for in gynecologists and obstetricians. However, there is little research evaluating medical residency programs, especially regarding qualitative reflective aspects. Thus, this descriptive and exploratory study, using quantitative and qualitative methods, aimed to evaluate the current Gynecology and Obstetric residency program of the the Catholic University of São Paulo (PUC-SP). This study combines comparative curricular analysis of the program recommended by the National Medical Residency Commission and the one offered by PUC-SP along with self-administered questionnaires for graduates from 2007 to 2018. The most significant finding of the comparative analysis are the discrepancies over the annual workload, showing overload in working hours; and the distribution of activities. The response rate to the questionnaires was 66% (41 respondents out of 62). The analysis showed a concentration of female respondents (n = 32, 78%), whose work activity is mainly located in the cities of Sorocaba (n = 21, 43.7%) and São Paulo (n = 10, 21%). A partial satisfaction with the program took by the graduates was prevalent (n = 34, 82.9%). Some responses also matched the findings of the comparative analysis between the programs, such as dissatisfaction with the number of gynecological surgical procedures performed (n = 39, 95.1%). As for the qualitative analysis of the written answers, graduates seem to appreciate activities in obstetrics. The most relevant complains were related to fewer hours for certain activities, especially to gynecological surgical practices and class activities. Based on the findings, suggestions for change that could have a positive impact of the residence program´s learning and teaching were proposed. This research contributes to the evaluation of a traditional medical residency program in Brazil, using replicable methodology and, therefore, can be used for others, so that improvements can be made